In vitro bioactivity evaluation, antimicrobial behavior and mechanical properties of cerium-containing phosphate glasses. (17th April 2019) - Youness, Rasha A; Taha, Mohammed A; El-Kheshen, Amany A; El-Faramawy, Nabil; Ibrahim, Medhat
Abstract: Na2 O–CaO–P2 O5 –CeO2 glasses have been prepared by melt-quenching method. Density and mechanical properties were measured. In order to evaluate bioactivity of the prepared glasses, they were immersed in simulated body fluid for different time intervals and then, samples were assessed via Fourier transform infrared spectroscopy, X-ray diffraction technique, transmission electron microscopy and selected area electron diffraction. The antimicrobial behavior of these glasses was evaluated against S. aureus, B. cereus, B. subtilis, E. coli and C. albicans . Furthermore, the successive increase of Ce contents had no detected negative influence on the bioactivity of the prepared glasses. On the other hand, the presence of Ce resulted in significant increase in density values and mechanical properties. Moreover, the antibacterial behaviors were enhanced significantly against E. coli and S. aureus as CeO2 contents increased. On the other hand, these glasses did not exhibit any antimicrobial behavior against B. cereus, B. subtilis and C. albicans. From the above results, it was concluded that these glasses can be applied in biomedical fields.